Types of Vegetation to Muffle Sound on Jalan Achmad A. Wahab - Wunarlan, Irwan; Idji, Berni (PT FORMOSA CENDEKIA GLOBAL, 2024)
One type of pollution that is invisible and abstract, namely noise, is a problem for city residents. This research aims (1) to try to prevent and improve noise on Jalan Ahmad A Wahab traffic, namely regulating the types of vehicles that cross Jalan Ahmad A Wahab at peak hours, (2) to plant various types of vegetation that can absorb sound energy. in various house yards near Jalan Ahmad A Wahab. Survey and observation methods are two methods used in research with a quantitative approach which is explained descriptively. There were 120 respondents and seven observation points in different locations. Next, the data was collected using a purposive sampling technique and analyzed using sound intensity levels, ear distance to the sound source and type of vegetation, followed by chi square analysis.